The Relation between Municipal and Government Bond Yields in an Era of Unconventional Monetary Policy - David Knezevic; Martin Nordström; Pär Österholm (Örebro University School of Business, 2019)
In this paper we investigate how the five-year Swedish municipal bond yield has been related to the corre-sponding yield on government bonds during the period that the Riksbank has conducted unconventional monetary policy in terms of bond purchases. Using daily Swedish data on bond yields from February 2015 to January 2018, we first conduct an event study to assess the short-run effects of the Riksbank's bond-purchase announcements. We then estimate bivariate vector autoregressive models in order to study the dynamic relationship between the yields. Results from the event study suggest that the accumulated short-run effect of the Riksbank's announcements was to lower the government bond yield by approximately 40 to 50 basis points and municipal bond yields by 30 to 35 basis points. Our vector autoregressive analysis indicates – in line with the event study – that an unexpected decrease in the government bond yield initially increases the municipal bond-yield spread. However, after approximately four weeks, the effect has been reversed and the municipal bond-yield spread is lower than it was initially. By conducting this analysis, we contribute to the understanding of the transmission of unconventional monetary policy.
Keywords: C32; E44; G10; 330; Spread; Event study; Vector autoregression; Cointegration